Co-Existence of TB & Leprosy in the same patient – A Case Report (TAJ: Journal of Teachers Association, 2010)
Leprosy is one of the more serious health issues in a number of developing countries. Although it seldom kills, leprosy is nonetheless a deforming, disabling and stigmatizing disease.1, 2 Tuberculosis is also a major public health problem affecting nearly one third of the global population. Though leprosy and tuberculosis are common infectious disease, yet co-infection of Mycobacterium leprae and Mycobacterium tuberculosis is rare possibly due to cross-immunity. A male patient of about 70 years presented with widespread shinny hypesthetic nodular lesions symmetrically located mainly in upper extremities, trunk and a little in lower extremities about 3 years back. Slit skin smear and histopathology studies showed significant amount of bacterial load which suggested lepromatous leprosy. About after one year of starting MDT treatment, the patient developed type-2 reaction of intermittent variety. During the episodic attacks of this reaction, the patient developed pulmonary TB supported by positive smear of sputum and patchy opacities of chest x-ray about 2½ years backTAJ 2010; 23(1): 103-105